Cinematic virtual reality film practice: expanded profilmic event and mode of production - Chan, Fong Yuen (Nanyang Technological University, 2023)
This research investigates the film practice of cinematic virtual reality (CVR), the adoption of virtual reality (VR) technology in filmmaking. With the rapid development of CVR, there are some new film practices formed and shared by filmmakers, as well as a growing amount of academic research studying on its on-screen aesthetics, attempting to theorise screen grammar to navigate audience attention responding to the designed storyline, as well as how to enhance their immersive experience with a sense of presence. However, there are few academic studies that focus on the film practice of CVR production which has fundamental differences compared to conventional filmmaking.